Klasifikasi Tanaman Herbal Menggunakan Metode Support Vector Machine - Agustina Meo1, Veronika; Uba Ladopurab, Yohana; R Kaesmetan, Yampi (Jurnal Teknik Informatika dan Desain Komunikasi Visual, 2024)
Herbal plants are plants that have value or health benefits, both traditional and scientific. Herbal plants have been used for centuries in various cultures as natural medicines, food supplements, or ingredients for body and health care. However, for many people they cannot differentiate herbal plants from other plants. With these problems, it is necessary There is an introduction to this problem with classification using the support vector machine method. . This research test uses test images that have been prepared previously, and calculated with GLCM using a pixel distance of d = 1 to 5 assisted by Gaussian and polynomial kernel functions. After performing feature extraction and classification calculations, the results showed that the highest accuracy was at pixel distance d = 1 with a polynomial function accuracy of 83%.